Exploring Ecofeminism through Cultural Narrative of Homelessness in Halaby’s Once in a Promised Land - Ashfaq, Tayyeba; Habiba, Umm e (Journal of Development and Social Sciences, 2024)
The study aims to investigate Ecofeminism through the cultural narrative of Homelessness in Halaby’s Once in a Promised Land. It investigates the Ecofeminist concept of Nature and Women dualism in Western philosophy, with a focus on the formation of a sphere of otherness through oppressions such as gender, race, and colonization. This qualitative study focuses on the interdependence of gender, nature, and women’s experiences in the global village proposed by Maria Mies and Vandana Shiva. Romanticizing and sentimentalizing nature is viewed as a third area in which modern people crave women, namely women’s bodies. The current understanding of nature has devolved into a deceptive process, with women perceived as inferior to men and their sexuality as subservient. Homelessness is a major issue in America, with Arab women like Salwa facing colonialism, homelessness, and refugee status. The study emphasizes the importance of accountability and self-awareness in navigating the complex dynamics of gender, nature, and women’s experiences for upcoming researchers.